Investors’ reactions to CSR reputation and disclosure assurance: an experimental analysis - Ernst, Carolin; Kunz, Jennifer; Fischer, Thomas; Ludwig, Laura (Journal of Management and Governance, 2025)
Corporate social responsibility (CSR) disclosures and a firm’s CSR reputation are important bases for retail investors’ judgments of legitimacy and their investment decisions. The present experimental vignette study with 300 participants acting as retail investors aims to provide deeper insights into the structure of these judgment processes. Our structural equation model reveals that a favorable CSR reputation and an assurance of the CSR disclosures positively affect whether values-driven motives are attributed to a firm’s CSR efforts, the perceived credibility of its CSR disclosures, and perceptions of its corporate social performance (CSP). In turn, perceptions of a firm’s CSP reinforces investors’ intention to invest, which in the end positively influences the amount of their investment. Our findings disentangle the complex cognitive processes involved, thus contributing to a better understanding of the combined effects of a firm’s CSR reputation and CSR disclosures on investors’ decision-making. In particular, these findings add to the scarce empirical research on individual legitimacy in investor decision-making and highlight the relevance of CSP as a decision parameter for investors, separate from corporate financial performance (CFP). Finally, the empirical results provide levers for managers to gain support from their firm’s investors and offer guidance for standard-setters and regulators regarding new disclosure requirement
Keywords: Assurance; Corporate social performance; CSR reputation; Individual legitimacy judgments; Investment decision